1982
DOI: 10.1073/pnas.79.8.2603
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of the Golgi apparatus and the microtubule-organizing center in cultured fibroblasts at the edge of an experimental wound.

Abstract: We have used the technique of experimental wounding of confluent monolayers ofnormal fibroblasts to induce essentially unidirectional and synchronous cell movement at the edge of the wound. The intracellular location of the Golgi apparatus and the microtubule-organizing center was determined by double indirect immunofluorescence microscopy, using antibodies specific for the membranes of the Golgi apparatus and antibodies specific for tubulin, respectively. In cells at the wound edge, the immunolabeled Golgi ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
286
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(297 citation statements)
references
References 25 publications
10
286
1
Order By: Relevance
“…Thus microtubules may be considered as sensors of directional changes that help maintain the centrosome in a position near the cell center where the microtubule system can respond quickly to rapid and sometimes gross changes in cell morphology in the course of cell movement. This may be important for the transport of secretory vesicles from the pericentrosomal Golgi apparatus to the leading edge (8,(38)(39)(40). Microtubules do not seem to serve, however, as effectors of directional cues generated by centrosomal repositioning.…”
Section: Resultsmentioning
confidence: 99%
“…Thus microtubules may be considered as sensors of directional changes that help maintain the centrosome in a position near the cell center where the microtubule system can respond quickly to rapid and sometimes gross changes in cell morphology in the course of cell movement. This may be important for the transport of secretory vesicles from the pericentrosomal Golgi apparatus to the leading edge (8,(38)(39)(40). Microtubules do not seem to serve, however, as effectors of directional cues generated by centrosomal repositioning.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we aimed to develop a cell line which could potentially act as a chemotactic gradient sensor to assist in characterization of the tumor microenvironment and metastatic process. Prior work by others has demonstrated that during in vitro wound closure involving either normal rat kidney, endothelial or rat embryonic cells, the Golgi complex (21,27,28), perhaps in close association with the microtubule-organizing center (27,29), precedes the nucleus during directed cell migration. However, not all studies are in agreement with these findings (30), and the orientation of the Golgi with respect to the nucleus may be both cell type and microenvironment specific.…”
Section: Discussionmentioning
confidence: 99%
“…This reorientation is closely coordinated with the reorientation of Golgi apparatus to the front of the nucleus. Both events occur rapidly after cell polarization (Etienne-Manneville and Hall, 2001;Gotlieb et al, 1981;Gundersen and Bulinski, 1988;Kupfer et al, 1983;Kupfer et al, 1982). In the cell rear, the increased PTEN activity is correlated with the activity of myosin II -an actin-dependent molecular motor that ensures the trailing edge contractility and retractive behavior.…”
Section: Basic Principles Of Cell Migration Overall Structure Of the mentioning
confidence: 99%